The Impact of Social Media Marketing on CAC Brand Loyalty of Samsung Smartphone Users in Jakarta: - - Adhitio Novanto Halim; Vita Briliana (International Journal of Economics, Business and Innovation Research, 2023)
The aim of this study is to analyze as well as to determine the impact of Social Media Marketing Activities (SM) as a predictor of Cognitive Brand Loyalty (CGL), Affective Brand Loyalty (AL), Conative Brand Loyalty (CNL), then Value Consciousness (VC), Brand Consciousness (BC) and Brand Love (BL) as mediating variables on Samsung smartphone users in DKI Jakarta. The objects used in this research is Samsung smartphones. The method used to select the sample in this study was convenience sampling and then 200 respondents who were buyers and users of smartphones from Samsung were taken. Then the method used in this study using SEM SMARTPLS3 . The results obtained in this study are that the SM variable has an influence on the VC, BC, and BL variables. The VC variable has no influence on the CGL, AL, CNL variables. The BC variable has an influence on CGL, AL, and CNL. The BL variable has an influence on CGL, AL, and CNL. The CGL variable has an influence on AL. The AL variable has an influence on the CNL of Samsung smartphone users in DKI Jakarta.